Evaluating Remimazolam for Procedural Sedation - Monanian, Genevieve; Yonel, Brandon; Rupert, Deborah; Razak, Alina; DeLemos, Michelle; Bergese, Sergio D. (Current Neuropharmacology, 2025)
Remimazolam, a novel short-acting benzodiazepine, has garnered interest in the realm of procedural sedation. Targeting a desired level of sedation requires a medication with both anesthetic and analgesic properties, particularly in non-operating room anesthetizing locations. Via gamma-aminobutyric acid type A receptor agonism, Remimazolam has demonstrated organ-independent metabolism and rapid time to both onset and recovery and has efficacy for procedural sedation in clinical trials. This article provides a review of the current literature on the utility of remimazolam for procedural sedation.
Keywords: depressed consciousness